On Message Dissemiaton and Event Detection in VANET - Ahmad Wani, Towseef; Singh, Yashwant (International Journal of Computer Sciences and Engineering, 2025)
The whole concept of message dissemination in Vehicular Ad hoc Networks relies on the inter-vehicle cooperation. This helpful nature of vehicles has empowered vehicles to gather and trade trafﬁc related messages continuously. In this manner, it is conceivable to utilize Vehicular Ad-hoc Networks for event discovery on urban roadways. Due to the uneven topology of urban roadways comprising of both major and auxiliary roadways, different protocols are designed. These protocols are designed to detect trafﬁc related events on roadways. Some protocols might be efficient for a particular road but may fail for some other types of roads. Besides, the current scattering strategies for occasions related data do not have the essential control system, so the message(information) might be dispersed to different geographical areas. This paper presents the review of existing message dissemination and event detection protocols in VANET. A tabular representation of various protocols of message dissemination and event detection on parameters like radio propagation model, transmission range, standard and simulator have been given. The comparative analysis of these existing protocols is also presented in the same section.